Development of Automatic Warning System for Water Salinity in Bangkachao, Thailand - Uma Seeboonruang; Virun Chulkaivalsucharit (My University, 2020)
Currently, local people, especially cultivators, suffer from poor water quality, that is, saline water, which has caused the recent reductions in crop yield and changes in land use.This issue can be ameliorated by gathering the necessary data and planning the best water management to avoid problems caused by poor water quality.A number of sluice gates and a manual water quality measurement system were built in many areas, such as Bangkachao, but issues were not resolved efficiently because data were not collected on time.To resolve this, we have developed a system providing telemetric measurements to detect salinity and water level values, which are simultaneously uploaded to a cloud server, and an online automatic warning system to classify data and provide instantaneous notifications online.This system can broadcast the data rapidly and automatically through the website (http://www.bangkachao-wateronline.com/) and LINE to inform the local cultivators about the situation and enable them to make plans on time.Moreover, the online warning system provides a database of the data with a filter feature to assist current and future water planning and protection.
Keywords: Early warning system; Water Quality Monitoring Technologies